Existence of Pranatal Education in Islam - Muktar; Mujiburrahman; Tarmidi; Masrur; Fajrurrahman; Suci Faradilla (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Prenatal education is often ignored in daily life. Though this education is highly recommended by religion for adherents of his religion. But to socialize prenatal education in social life today, it is necessary to re-actualize knowledge about the existence of prenatal education. Community life will gradually improve by paying attention to prenatal education as one of the needs in educating children from the womb in an Islamic perspective. There are two problems that must be answered in this paper are the stages of human creation and the concept of prenatal education in Islam. This research is in the form of library research, in which the research aims to describe the meaning on the basis of understanding the reading material sourced from the literature which has a close relationship with the problems presented in this paper using descriptive qualitative methods aimed at describing and analyzing phenomena and concepts using words not numbers. This study aims to determine: the development of prenatal age children, the concept of Pranatal education in Islam. The data collection technique used is to examine a number of primary and secondary data sources. Data analysis techniques by means of text analysis (content analyst). The results showed that: 1. The development of a prenatal child during her mother's womb includes three stages, including the Nuthfah stage in the form of male sperm and female egg cells that meet in the womb and fertilization occurs. The second stage ‘Alaqah (a clot of blood) even though the body tissue has begun to form, the next stage is the Mudghah (a lump of flesh), at this time in the form of a fetus that has been perfect and lives with spirits blown by angels. 2. The concept of prenatal education includes 3 stages: first, the preconception period (partner selection), second, the postconception period (marriage / copulation), third, the pre-natal period (pregnancy). Based on the results of this study is expected to be an information or input to parents to pay more attention to education to children, especially educating children since in the womb, based on certain concepts and methods with the hope that children born will become human figures who have noble personality, as expected.